2004
DOI: 10.1111/j.1365-2265.2003.01987.x
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine levels in Cushing's syndrome; elevated resistin levels in female patients with Cushing's syndrome

Abstract: Here we report for the first time that resistin levels are significantly elevated in CS patients and may be important in the insulin resistance associated with glucocorticoid excess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 51 publications
6
44
0
3
Order By: Relevance
“…Resistin is significantly higher in female CS patients than in female control subjects and does not significantly change after cure, despite improvement of obesity and metabolic profile (116). TNFa levels are unchanged in CS (115).…”
Section: European Journal Of Endocrinologymentioning
confidence: 85%
See 1 more Smart Citation
“…Resistin is significantly higher in female CS patients than in female control subjects and does not significantly change after cure, despite improvement of obesity and metabolic profile (116). TNFa levels are unchanged in CS (115).…”
Section: European Journal Of Endocrinologymentioning
confidence: 85%
“…Leptin does not seem to be acutely affected by the cortisol drop following neurosurgery but it has been found to be decreased in patients after long-term remission (116).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…In human medicine, a study found that patients with Cushing's syndrome had lower adiponectin levels than the controls, which suggests that hypercortisolemia directly affected the adiponectin levels independent of body weight 43. However, another study reported that the serum adiponectin levels in patients with Cushing's syndrome did not differ from those in the control group and they were not changed significantly after hypophysectomy, despite a significant decrease in the body fat mass, insulin resistance, and cortisol 36, 44. In veterinary medicine, a recent study showed that the circulating adiponectin concentrations in 20 PDH dogs with blindness were significantly lower than those of 20 healthy dogs 18.…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributable to the persistence of hypercortisolemia for parts of each day, and to persistently higher visceral fat mass after the treatment. In human studies, subjects with Cushing's syndrome have persistent central fat mass, higher leptin concentrations, and other abnormal adipokines, even after long‐term cure 35, 36. Therefore, it is possible that the maintenance of hyperleptinemia might have been the result of secretion of leptin by the persistent central fat mass in dogs with PDH.…”
Section: Discussionmentioning
confidence: 99%
“…Since visceral adipose tissue is considered to be the major source of adipokines, the increase in visceral fat mass with the resultant increase in plasma adipokine levels may at least partly be responsible for the occurrence of insulin resistance in cushing syndrome with glucocorticoid excess. indeed, glucocorticoid is shown to stimulate the release of resistin from mouse adipocytes [10], and serum resistin levels are elevated in cushing syndrome [11], indicating that resistin may be involved in the glucocorticoid-induced insulin resistance.…”
Section: Evaluation Of Metabolic Parameters In Crh-tg Micementioning
confidence: 99%